Pengendalian Mutu Produk Kemeja Wanita Menggunakan Metode Statistical Process Control pada UMKM Konveksi - Nuryono, Arif; Zulkarnaen, Iskandar; Apriyani, Apriyani; Nugroho, Oki Widhi; Kurnia, Hibarkah (Universitas Suryakancana, 2025)
Convection Micro, Small, and Medium Enterprises (MSMEs) still experience product defects outside the target. This is because there is a control system that has not been implemented properly. MSME Konveksi is pursuing a large number target due to orders from customers. However, when sending products to customers, product defects are still found, meaning that there is no product control by the manufacturer. This research aims to control the quality of products sent to customers. This research method uses a combination of the Plan Do Check Action (PDCA) approach with the Statistical Process Control (SPC) method. This research found that there were four categories of defects in the MSME Konveksi production process, namely loading, sewing, rubbing, and name tag dimensions. The most dominant problems are sewing defects and loading defects at 85%. Meanwhile, the results of the P-chart analysis show that there are 4 data in the production process in Sep-Dec 2022 that exceed the upper control limit. This research cumulatively resulted in a reduction in defects from 5.84% to 3.19%, meaning a decrease of 45.4%. Meanwhile, dominant defects, namely sewing defects, decreased by 30.8% and loading defects decreased by 24.5%. Meanwhile, the results of the P-chart analysis after improvements showed no deviation in the percentage of defects during 2023. This research has been successful in reducing production defects so that Konveksi MSMEs can increase the percentage of products with quality according to customer orders. Usaha Mikro Kecil dan Menengah (UMKM) Konveksi masih terjadi adanya cacat produk di luar target. Hal ini dikarenakan adanya sistem pengendalian yang belum diterapkan dengan baik. UMKM Konveksi mengejar target jumlah yang banyak karena pesanan dari pelanggan. Namun dalam pengiriman produk ke pelanggan masih ditemukan adanya cacat produk, artinya belum ada pengendalian produk oleh produsen. Penelitian ini bertujuan untuk mengendalikan kualitas produk yang terkirim ke pelanggan. Metode penelitian ini menggunakan kombinasi pendekatan Plan Do Check Action (PDCA) dengan metode Statistical Process Control (SPC). Penelitian ini menemukan terdapat empat kategori kecacatan pada proses produksi UMKM Konveksi, yaitu loading, penjahitan, gosok, dan dimensi nametag. Permasalahan yang paling dominan adalah cacat penjahitan dan cacat pemuatan sebesar 85%. Sementara hasil analisa P-chart terdapat 4 data dalam proses produksi pada bulan Sep–Des 2022 yang melebihi batas kendali atas. Penelitian ini secara kumulatif menghasilkan penurunan cacat dari 5.84% menjadi 3.19%, artinya turun 45.4%. Sementara untuk cacat dominan yaitu cacat penjahitan turun sebesar 30.8% dan cacat loading turun 24.5%. Sementara hasil analisa P-chart sesudah perbaikan tidak terdapat adanya penyimpangan persentase cacat selama tahun 2023. Penelitian ini sudah berhasil dalam mengurangi cacat produksi, sehingga UMKM Konveksi dapat meningkatkan jumlah persentase produk dengan kualitas sesuai pesanan pelanggan.